2020
DOI: 10.1080/14737140.2020.1810572
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection and risk factors in the changing treatment landscape of metastatic renal cell carcinoma

Abstract: Introduction: The approval of combination treatments for metastatic renal cell carcinoma (mRCC) represents a major change in the clinical management of this malignancy. Updated treatment guidelines differentiate first-line mRCC treatment by patient risk group as defined by prognostic models and the number of risk factors. Areas covered: Current prognostic models, with a focus on the International Metastatic RCC Database Consortium and the Memorial Sloan Kettering Cancer Center models, the heterogeneity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The variety of available life-prolonging CPI-based treatment combinations has made treatment decisions challenging, as these combinations have not been compared to each other. The treatment is chosen to take into account the patient's clinical condition [29] and the risk group as defined by Heng's criteria developed in 2009 in a completely different clinical scenario when the main treatment options were VEGFRi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variety of available life-prolonging CPI-based treatment combinations has made treatment decisions challenging, as these combinations have not been compared to each other. The treatment is chosen to take into account the patient's clinical condition [29] and the risk group as defined by Heng's criteria developed in 2009 in a completely different clinical scenario when the main treatment options were VEGFRi.…”
Section: Discussionmentioning
confidence: 99%
“…We included clinical, pathological, and laboratory values. Future prognostic models for CPI combination therapies may be enhanced by the inclusion of genetic markers or gene signatures, but these are currently clinically unavailable [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, due to numerous linguistic, cultural, and geographical similarities, there is cooperation between UCR scholars and Arab nations such as Egypt and, more recently, Jordan. Dawood, S., affiliated with the Department of Medical Oncology, Dubai Hospital, Dubai, U.A.E., created strong networks with Kuwait [ 44 ], Oman [ 45 ], Egypt, Saudi Arabia [ 46 ], the UK [ 47 ], and the USA [ 48 ]. The current study's pattern of international collaboration aligns with previous bibliometric studies conducted on cancer in the Arab world, as indicated by Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, cell cycle, cisplatin, MCF-7, p53, anticancer, colon cancer, hepatocellular carcinoma, and DNA damage, and lung cancer are the backbone terms of the green cluster. The research focus of this knowledge domain spotted light on the discovery of new anticancer agents and utilization of in vitro cancer models [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ]. Researchers in UAE have investigated the apoptotic effects of various compounds on cancer cells.…”
Section: Discussionmentioning
confidence: 99%